Survey on integration of cloud computing and WSN to identify best Cloud service provider - M, Ms.Vedambika; Rani S, Ms. Soja (IJRDO -Journal of Computer Science Engineering, 2016)
ireless Sensor Networks are used to sense the environment conditions and collect the information. The collected information is stored in the cloud in which the user can access the required information. The integration of both cloud service provider and sensor network provider will provide the effective service to the cloud service user. This paper is a general survey of all the sensor network provider and cloud service provider integration. The majority of the survey is mainly focused on the authenticated trust and reputation calculation for sensor network provider and cloud service provider